A new species of Lathrobium from Kyrgyzstan (Coleoptera, Staphylinidae: Paederinae) - Assing, Volker (Zootaxa, 2007)
The Holarctic genus Lathrobium Gravenhorst, 1802 is represented in the Palaearctic region sensu Löbl & Smetana (2004) by five subgenera. According to the Palaearctic catalogue (Smetana 2004) and an updated version by Schülke (unpubl.), the highly diverse nominal subgenus currently includes 248 valid species and subspecies in the Palaearctic region (6 nomina dubia not included), with 73 (sub-)species confined to the Western Palaearctic (one of these species present also in the western parts of the Eastern Palaearctic), 167 (sub-)species to the Eastern Palaearctic including Middle Asia (two of them present also in the eastern parts of the Western Palaearctic), and with 8 species having a trans- Palaearctic distribution. Several species have become known from Middle Asia (Uzbekistan, Tajikistan, Kazakhstan), but up to today no representative of the genus has been reported from Kyrgyzstan (Smetana 2004).